Unpalatability of Hyla semilineata tadpoles (Anura) to captive and free-ranging vertebrate predators - D'Heursel, A.; Haddad, CFB (Universita Degli Studi Di Firenze, 1999)
This study examines the unpalatability of Hyla semilineata tadpoles, relating this possible defence mechanism to their black, presumably aposematic, colouration. Bullfrog tadpoles (Rana catesbeiana), similar in size to the H. semilineata larvae, were used as controls in the experiments. The palatability of H. semilineata tadpoles was tested by offering the tadpoles to Fish (Hoplias malabaricus), free-ranging passerine birds (Pitangus sulphuratus) and hawks (Buteo magnirostris), and domestic chickens (Gallus domesticus). All predators showed a significant preference towards the control R. catesbeiana tadpoles. However, in experiments with fish, this preference was not significant for tadpole capture, only for their ingestion, suggesting that the fish could not distinguish between the two species before tasting them. Although great kiskadees (P. sulphuratus) preferred the control R. catesbeiana tadpoles, they promptly ingested more than half of the test H. semilineata tadpoles when these were offered alone. The chickens, used as naive predators, clearly learned to avoid the black H. semilineata tadpoles after a few trials. The conspicuous colouration and unpalatability of H. semilineata tadpoles may benefit the individual as well as the group, depending on the predator involved.
Keywords: Anura; Hylidae; palatability; predators; tadpole